A novel peroxymonosulfate (PMS)-enhanced iron coagulation process for simultaneous removal of trace organic pollutants in water. (15th October 2020) - Wang, Yu; Pan, Tao; Yu, Yafei; Wu, Yang; Pan, Yanheng; Yang, Xin
Abstract: Conventional coagulation process is not effective to eliminate trace organic compounds (TrOCs). This study proposed a novel peroxomonosulfate (PMS) amended iron coagulation process and found its effectiveness in eliminating TrOCs in synthetic and natural waters. In synthetic waters containing hydroquinone (HQ) or benzoquinone (BQ), Fe(III)/PMS effectively degraded carbamazepine (CBZ), a representative of resistant TrOCs. The step of reduction of Fe(III) to form Fe(II) governed the degradation rate of CBZ as PMS activation by Fe(II) was the dominant reaction to generate SO4 -, which was the major reactive oxidant in the system. Meanwhile, HQ was quickly transformed to BQ in the Fe(III)/PMS system and BQ acted as an electron shuttle to induce Fe(III)/Fe(II) redox cycle and accelerate PMS activation. Natural organic matter (NOM) bearing phenolic and quinone moieties played similar roles as HQ and BQ and fast CBZ degradation was also observed. Finally, two surface waters spiked CBZ were subjected to bench-scale experimentation to simulate coagulation/flocculation/sedimentation processes in water treatment plants. Compared to the conventional iron coagulation process, the PMS-amended iron coagulation process increased the removal percentage of CBZ by 50%–80%. Overall, this study demonstrates that PMS enhanced iron coagulation is a promising process for the abatement of TrOCs in water treatment. Graphical abstract: Image 1 Highlights: SO4 . - was the dominant reactive specie in HQ/Fe(III)/PMS and BQ/Fe(III)/PMS systems. BQ acted as an electron shuttle to accelerate iron redox cycle and PMS activation. CBZ in river waters was effectively removed by PMS-amended iron coagulation process. NOM played an important role in accelerating CBZ removal.